Den planetære vending: En fremtid for sammenlignende litteraturforskning? - Andersen, Frits (K&K - Kultur og Klasse, 2019)
Leading scholars of Comparative Literature Susan Friedman and Gayatri Chakravorty Spivak have proposed planetarity as a paradigm for research that captures the linguistic, economic and ecological complexity of the planet better than concepts such as, for example, the global and world literature. The article is a critical dialogue with Amy Elias and Christian Moraru’s The Planetary Turn. Relationality and Geohethetics in the Twenty-First Century (2015), an ambitious attempt to gather a highly heterogeneous field of theories of the functioning of literature and art in emergent forms of global relationality and new volatile political communities. The planetary reading perspective involves special attention to scale and employs combinations of macroscopic and microscopic analytical strategies, which the article seeks to show through a comparative mapping of patterns in clusters of texts around Joseph Conrad’s Heart of Darkness and the Virunga National Park in DR Congo.